2008
DOI: 10.1071/wr07159
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release components of PZP contraceptive vaccine extend duration of infertility

Abstract: Successful immunocontraception of wildlife relying on repeated access to individuals for boosters has highlighted the need to incorporate primer and booster immunisations into one injection. We have investigated use of controlled-release polymers (lactide-glycolide) in small pellets to provide delayed in vivo delivery of booster porcine zona pellucida (PZP) antigen and adjuvant. This report reviews pellet-making methodology, in vitro testing of controlled-release pellets and in vivo effects of controlled-relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Efforts to create longer‐lasting contraceptive vaccines with increased efficacy have involved modifying formulations (Henderson et al , Botha et al ), adjuvants (Allison and Gregoriadis , Gupta et al , Lyda et al ), and delivery matrices (Turner et al , ; Killian et al ). Previous studies have demonstrated a positive correlation between levels of pZP antibodies produced and contraceptive effect via binding of sperm receptor sites (Liu et al , Turner et al ); however, other contraceptive mechanisms of action may involve altered ovarian function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to create longer‐lasting contraceptive vaccines with increased efficacy have involved modifying formulations (Henderson et al , Botha et al ), adjuvants (Allison and Gregoriadis , Gupta et al , Lyda et al ), and delivery matrices (Turner et al , ; Killian et al ). Previous studies have demonstrated a positive correlation between levels of pZP antibodies produced and contraceptive effect via binding of sperm receptor sites (Liu et al , Turner et al ); however, other contraceptive mechanisms of action may involve altered ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…Mares treated with a 1‐ml injection of 65‐µg pZP in a Freund's complete adjuvant (FCA) emulsion and the simultaneous injection of booster pellets designed to release pZP antigens at 1 month, 3 months, and 12 months had annual reproductive rates for 2001–2004 of 5.9%, 14.0%, 32.0%, and 47.5% compared to an average of 53.8 ± 1.3% for untreated mares (Turner et al ). However, the effectiveness of the slow‐release pellets has been inconsistent (Turner et al , Ransom et al ). SpayVac® (ImmunoVaccine Technologies, Inc. [IVT], Halifax, NS, Canada) is a pZP vaccine that uses a unique liposome technology (DepoVax®) and has delivered single‐dose, long‐lasting immunocontraception in a variety of species including fallow deer ( Dama dama ; Fraker et al ) and gray seals ( Halichoerus grypus ; Brown et al 1997 a ).…”
mentioning
confidence: 99%
“…The matrix used thus far has incorporated various ratios of lactide-glycolide, either in the form of microcapsules 81 or in the form of small pellets that can be injected either by hand or by dart. [82][83][84] Results thus far have been encouraging, but not definitive, and a great deal of variability in both the manufacturing process and the results has resulted. Another difficulty with this approach is that it has not been possible to incorporate powerful oil-based adjuvants in the microcapsules and pellets.…”
Section: Duration Of Contraceptive Actionmentioning
confidence: 99%
“…The development of a novel, safe and effective adjuvant (AdjuVac, National Wildlife Research Center, Fort Collins, CO, USA) combined with PZP-based vaccine succeeded in rendering animals of several species infertile for several years after a single dose (Table 1). Injectable formulations of PZP vaccines, such as the proprietary liposome-containing product SpayVac (ImmunoVaccine Technologies, Inc., Halifax, NS, Canada), with controlled-release properties, have been developed that generate responses for multiple years following a single administration (Brown et al 1997;Turner et al 2008;Rutberg et al 2013). Modified FCA has also been used as a safe, effective substitute for FCA (Lyda et al 2005).…”
Section: Immunocontraceptive Vaccinesmentioning
confidence: 99%